Viability of peach palm by-product, Spirulina platensis, and spinach for the enrichment of dehydrated soup - Los, Paulo Ricardo; Simões, Deise Rosana Silva; Leone, Roberta de Souza; Bolanho, Beatriz Cervejeira; Cardoso, Taís; Danesi, Eliane Dalva Godoy (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to develop dehydrated soup formulations using flour from peach palm by-product (PPB), Spirulina platensis or spinach, as well as to evaluate their composition by physical, chemical, instrumental, and sensory methods. Four formulations were developed: standard, PPB flour, PPB flour and S. platensis, and PPB flour and spinach. The samples were analyzed for proximate composition, chlorophyll content, total phenolic compounds, antioxidant activity, color, viscosity, water absorption, and microbiological parameters. The sensory characterization was performed by the check-all-that-apply method. The soups containing spinach or S. platensis presented the highest protein contents of 3.3 and 4.6 g 100 g-1, respectively. The soups formulated with the microalgae S. platensis showed higher contents of fibers, lipids, and antioxidants. Changes were observed in the color and viscosity of the soups. The standard dehydrated soup was characterized as shiny, creamy, with seasoning flavor and fragments, and a pale-yellow color; the formulation with spinach, as grainy, with an herb odor and flavor, seasoning fragments, and a dark-green color; and with S. platensis, with herb flavor, seasoning fragments, and a dark-green color. The developed formulations are within the microbiological standards for food established by the Brazilian legislation. The sensory analysis revealed a new market niche, and the soups containing PPB and S. platensis showed good acceptability. Peach palm flour, Spirulina platensis, and spinach are alternatives for the nutritional enrichment of dehydrated soups with high protein, ash, fiber, and antioxidant contents.